Evaluation of The Implementation of The Provision Policy Professional Allowances for ASN And Non ASN Teachers at All Levels Junior High School - Retor, Wanda M. G.; Rawis, Joulanda A. M.; Sumampow, Zoya F. (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The purpose of this study was to evaluate the effectiveness of the implementation of the policy of providing professional allowances for civil servants and non-civil servant teachers at the regional level in Manado City, and to identify the obstacles faced in implementing the policy. This study employed a qualitative case study approach, which refers to field notes and does not involve numerical data, but rather relies on information obtained based on the situation on the ground. The results indicate that the implementation of the teacher professional allowance distribution system in Manado City still faces technical and administrative challenges. Regulations for the distribution of teacher professional allowances are formally available but have not been fully understood and optimally implemented by all relevant parties. The disbursement of professional allowances for civil servant teachers is more stable than for non-civil servant teachers due to their adherence to the national civil service system and central regulations. Monitoring and evaluation of the implementation of allowance distribution remains ineffective, both by the education office, the inspectorate, and external supervisory institutions. Improvements to information systems, increased human resource capacity for data management, and regulatory refinements are needed to better adapt to field conditions.